COMPARATIVE ANALYSIS OF PRODUCTION PREDICTION OF SILUNGKANG SONGKET AND PANDAI SIKEK SONGKET WITH MAMDANI FUZZY INFERENCE SYSTEM (FIS) METHOD - Devia Kartika; Rima Liana Gema (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
Fuzzy logic is widely applied in various fields, such as industry, communications, etc. Fuzzy logicwas developed to solve an obscure problem. The problem that arises in the production at MSMEsSongket Silungkang and Songket Pandai Sikek at this time is that there is no system used as areference in determining the amount of production in the future. Where this method can utilizedemand and supply data in the past which is then processed with fuzzy stages so as to produceproduction figures. The government has prioritized the development of the Silungkang songkethandicraft business, which is a regional specialty, in order to enter the export market. In the earlystages, the priority of the regional government was to increase the production of craftsmen byfacilitating coaching for micro, small and medium enterprises (MSMEs), especially those engaged insongket crafts, to continue to be developed by increasing quality and creativity. By applying theFuzzy Inference System method in predicting the production of Songket Silungkang KotaSawahlunto and Songket Pandai Sikek Kota Agam can help several parties such as the government,micro, small and medium enterprises in making efforts to handle and make good decisions towardsincreasing the production of Songket MSMEs in each region. and can provide a comparison of thepredicted results of production for the coming period so that it can produce the optimal number ofsongket based on market demand.